Design, ADME study, and molecular docking of serine derivatives of isatin – para-aminobenzoic acid conjugates - H. Abdulsada, Abbas; Kareem Al-yassery, Hawraa; Raad Abdulkareem, Zahraa; Hatem Hasan, Saja (Pharmakeftiki, 2025)
A total of 20 novel isatin – para-aminobenzoic acid derivatives of serine have been designed in order to assess their potential effectiveness against some promising targets. Molecular docking was accomplished with the crystal structure of some of the predicted targets (i.e., 5UEN, 5FL4, 6QNG, 5SDB, and 6SUK), and we analysed the binding affinity between the compounds and each of the proteins of interest. Moreover, absorption, distribution, metabolism, and excretion (ADME) studies were conducted for the compounds with the best docking poses, thereby providing sufficient information about their pharmacokinetic, physicochemical, and drug-likeness properties.